Synthetic essentiality of TRAIL/TNFSF10 in VHL-deficient renal cell carcinoma - Xuechun Wang; Yujing Qin; Loan D. Duong; Minzhi Liang; Adrian Chao; Rossella Parrotta; Yaoyin Li; Paresh Kumar Purohit; Yihao Fang; Guoqiang Liu; Jianping He; Jiling Wen; et al. (Proceedings of the National Academy of Sciences, 2026)
Clear cell renal cell carcinoma (ccRCC) is the most common and aggressive subtype of kidney cancer. Loss of von Hippel–Lindau (VHL) and the consequent activation of hypoxia-inducible factor-α (HIFα, especially HIF2α) plays an essential role in ccRCC initiation and progression. The VHL–HIF2α axis as the main driver for ccRCC may present specific opportunities to control the disease by cotargeting HIF2α with belzutifan and another vulnerability. This study elucidates the synthetic essentiality of TRAIL (tumor necrosis factor-related apoptosis-inducing ligand) in VHL-deficient ccRCC. Upregulated in ccRCC in a VHL–HIF2α-dependent manner, TRAIL is selectively essential in ccRCC cells, promoting cell proliferation by activating the p38 MAPK pathway and facilitating G1/S phase transition. Depletion of endogenous TRAIL or inhibition of HIF2α with belzutifan sensitizes ccRCC cell and tumor models to recombinant TRAIL, presenting a promising avenue for combination therapy in ccRCC.